Writing Online: An Analysis on the Features of Students’ Blog Posts - Cantina, Jovelyn M. (Future Science / FSH-PH Publications, 2022)
Writing online has influenced the way people communicate and write. The integration of this innovative electronic device into the language classroom provided students with writing opportunities. This study aims to analyze the features of the students’ blog posts. This study employed a general qualitative approach utilizing the blog posts of the BSED second-year students enrolled in a language class, which were drawn randomly as the corpus of the study. The content analysis technique was used to characterize a student's blog post. The study revealed that the features of the students’ blog posts were blogging attitude, content, connections with the audience, and innovativeness. Student bloggers communicated to the readers with excitement, motivation, interest, or emotions. Student bloggers generated ideas, opinions, concepts, and thoughts about the topic, provided useful and important information from various sources, and took a position on the topics and concepts that were discussed. Furthermore, students communicated in innovative ways by using figurative language, idioms, and powerful words. This study concluded that blogging is a trend in writing that allows creativity and an opportunity for students to improve their writing skills. Thus, the teacher may use blogging as one of the flexible assessments that can be utilized in the new normal of teaching by evaluating the authentic work of the students. Students may also be given an infographic called